Concept for Automatic UI Generation for Hierarchical XML Structures in PLM Systems Based on a Hybrid Data Model - Mariusz CHOLEWA (Communications of International Proceedings, 2025)
This paper presents a initial concept for automatic user interface (UI) generation for multi-level hierarchical data structures (e.g., BOMs, variants, revisions) in PLM systems. It builds on a hybrid data model combining RDBMS and XML and on an MVC → XML → XSLT → HTML rendering pipeline previously demonstrated in the PROEDIMS environment. We propose: (1) a metamodel of tree-based views (NodeView, ChildrenRegion, RelationView, AggregateView), (2) declarative XML→component mapping rules with context inheritance and support for lazy-loading/pagination, and (3) a sketch of an XML→UI dependency graph enabling local refresh of affected interface fragments. The approach preserves a single source of truth (domain templates) for both data and UI, reducing time-to-screen as the model evolves (e.g., sustainability extensions: carbon/water footprint, recycling, Scope 1–3) while limiting engine-level changes. This is a vision paper: it formulates assumptions, architecture, and usage scenarios and identifies benefits and risks (e.g., deep-XML processing costs, XPath rule complexity, variability of XML support in RDBMS), leaving quantitative validation of a prototype for future work.
Keywords: PLM; XML; XSLT; MVC; BOM; automatic UI generation; hierarchical data.